Influence of shrinkage on the dynamic properties of a cross-laminated timber panel - Thomas Furtmüller; Marco Kendlbacher; Fabian Huber (Results in Engineering)
In this paper, experimental modal analyses of a cross-laminated timber (CLT) panel with three layers subjected to free-free boundary conditions are presented. The present study aims at investigating the effect of changing moisture content on dynamic properties of CLT both experimentally and numerically. Two experimental campaigns with a difference in the average moisture content of the test specimen of 2.7% were analyzed. Although the mass of the specimen is reduced by drying, natural frequencies decrease significantly. The apparent loss of stiffness is attributed to opening of narrow face joints due to shrinkage. This effect introduces additional nonlinear artifacts in the measurement data not complying with linear modal analysis. Using a higher-order shear deformable plate theory in a Finite Element model updating framework, experimental natural frequencies and mode shapes are reproduced satisfactorily covering a wide frequency range. As an outcome of the numerical simulations assuming homogeneous material behavior without directly modeling the narrow face joints, a reduction of the in-plane and out-of-plane shear moduli of the boards constituting the panel of 9 and 16% due to shrinkage, respectively, is identified, while Young's moduli remain almost unaffected. In a simplified analytic model of the plate the occurrence of the observed nonlinear disturbances is explained qualitatively by harmonic frequency generation of a single-degree-of-freedom oscillator with piecewise linear spring stiffness. The study highlights the complexity of the material behavior of CLT panels even for simple geometries without boundary effects and the potentially grave effect of drying shrinkage on the vibration characteristics of these structures.